Accountability Asset Recovery: A Leadership & Sustainability Initiative Receivership Is NOT Releasership - Sheldon-London, Monika L. (Journal of Leadership, Accountability and Ethics, 2021)
For effective recovery of qualified assets, receivership is not releasership--the improper disposition of recovered assets. Disposition of assets being the technical terminology utilized by asset recovery and insolvency practitioners to motion the court to release recovered assets held in their custody. According to the IMF, insolvency practitioner overreach has become macro-critical to the stability of the global financial system. Anti-money laundering, countering the financing of terrorism, preventative measures and the proceeds of crime acts, 2003 and 2009 for the common law legal system and 2005 for the civil law legal system under pinning AML-CFT international cooperation could have become captured for personal purposes by the participants in the very network groups involved in its creation. Investigating the relationship through the lens of Operation Rotten Tomato, the case studying conversion, through Chapter 11 Bankruptcy, of property qualified for recovery based on suspicion or reasonable grounds to suspect unproven wrongdoing. Implementation of the United Nations Convention Against Corruption a systemic experimentation in public policy failure, information asymmetry and principal agent problems.